Pola Penyelesaian Sengketa Waralaba Produk Teh Poci Di Ponorogo - Djayadi, Haris (Institut Agama Islam Negeri Ponorogo, 2021)
The purpose of this study is first to find out the pattern of dispute resolution in the franchise practice of Teh Poci, the second is to describe what the ideal pattern should be. In accordance with the characteristics of the existing problems, the most relevant form of approach to analyzing the above problems is empirical legal research. This research sees law as a reality in society, meaning how the law is practiced. The settlement of default on the agreement in the Tea Poci product franchise business in Ponorogo is the cancellation of the contract as a result of default and is settled on the principle of peace, namely by consulting and negotiation techniques. Ideally, under such a mechanism the franchisor should develop an internal procedure for handling complaints. However, this procedure is not stipulated in the franchise agreement and meets certain minimum standards. This standard should provide a procedure for resolving disputes. If a dispute arises, either party can initiate a complaint handling procedure under the Code of Conduct, or under a franchise agreement.